Pemanfaatan Aplikasi Liveworksheet sebagai Referensi Membuat LKPD di SDN 9 Menteng Palangka Raya: Utilization of Liveworksheet Application as a Reference for Creating LKPD at SDN 9 Menteng Palangka Raya - Afrom, Ichyatul; Dilla, Widya Permata; Azahari, Abd Rahman; Sapriline, Sapriline; Femmy, Femmy; Nurhalisa, Nurhalisa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Quality education requires innovation in teaching methods by utilizing technology. The challenges often relate to limited resources and the selection of learning methods to engage students and enhance their motivation to learn. As information technology evolves, the use of digital media in learning becomes increasingly relevant. However, many teachers are still not skilled in utilizing digital applications in the learning process. Therefore, training and assistance for teachers are necessary to optimize the use of Liveworksheet in developing Lembar Kerja Peserta Didik (LKPD). This activity aims to enhance the competencies of teachers at SDN 9 Menteng Palangka Raya. It was conducted over two meetings involving classroom teachers and subject teachers. The method used was direct instruction, with in-depth material exploration in the first meeting and practical assistance in the second meeting. After the activity was completed, a reflection session was held with the participants, indicating that they were satisfied with the training. The majority of participants expressed that they gained not only an understanding of how to utilize Liveworksheet but also improved their skills in creating more interactive and engaging LKPD. Additionally, participants reported that the material presented was highly relevant to their classroom needs and helped boost their confidence in using technology in the learning process.